American issues : a documentary reader - Dollar, Charles M.; Reichard, Gary W., 1943- (New York : Glencoe, 1994)
A collection of primary, secondary, and visual source documents on American history, covering the period from early exploration of the New World to present times.
Keywords: United States -- History -- Sources; United States -- History; United States -- History -- Sources